Kinanthropometric profile of Cuban women Olympic volleyball champions - Carvajal, W.; Betancourt, H.; León, S.; Deturnel, Y.; Martinez, M.; Echevarria, I.; Castillo, M. E.; Serviat, N. (MEDICC Review, 2012)
Athletes' kinanthropometric profiles are widely addressed in the scientific literature. Such profiles are particularly important in volleyball because absolute size contributes a significant percentage of total variance associated with athletic success. As in other team sports, volleyball players' kinanthropometric attributes correlate with the game's tactical demands. From 1992 through 2000, the Cuban women's volleyball team achieved top global performance, winning first place in three successive Summer Olympic Games.